Grandparents raising their grandchildren: Implications for the vulnerable children of Eswatini - Ncamsile D. Motsa; Pholoho J. Morojele (South African Journal of Childhood Education, 2022)
Background: Studies have shown that caregivers’ economic constraints and emotional burdens have a negative implication both on their well-being and that of their children. For children raised by grandparents, age is also an additional dynamic that not only affects the grandparents but also affects the children they raise and other family members. However, poverty, HIV infection and AIDS have forced many children in Eswatini (formerly, Swaziland) to be in the care of their grandparents, hence raising concerns about their educational focus and achievement.